1999
DOI: 10.1046/j.1525-1438.1999.99029.x
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin, radiation, and amifostine in carcinoma of the uterine cervix

Abstract: A pilot, open, comparative study was performed on patients with locally advanced cervical cancer to investigate the efficacy and safety of amifostine. Twenty patients with a histologic diagnosis of squamous cervical cancer were treated with radiotherapy and randomized in two groups. Group A received cisplatin at 20 mg/m2 for five days in two cycles during intracavitary radiotherapy and 100 mg/m2 x 2 cycles during external radiotherapy, and amifostine 825 mg/m2 15 min before the cisplatin infusion. Patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Our result that amifostine is extremely effective in treating both overall and severe neurotoxicity is supported by the findings of various clinical trials (14, 16, 36). However, there is one exception that reports that amifostine is not able to have a preventive role in neuropathy (38).…”
Section: Discussionsupporting
confidence: 85%
“…Our result that amifostine is extremely effective in treating both overall and severe neurotoxicity is supported by the findings of various clinical trials (14, 16, 36). However, there is one exception that reports that amifostine is not able to have a preventive role in neuropathy (38).…”
Section: Discussionsupporting
confidence: 85%
“…There are successful in vitro results supporting amifostine neuroprotection against cisplatin [120], as well as against oxaliplatin [122]. Some clinical data, with different levels of reliability (Table 3), indicated that amifostine exerts some protection against peripheral neurotoxicity of carboplatin plus paclitaxel combination therapy [127][128][129]131], oxaliplatin [126], and cisplatin [133,134], whereas two other studies have failed to show significant neuroprotection against carboplatin plus paclitaxel combination therapy [130] and cisplatin [132] (Table 3). BNP7787 (Dimesna, Tavocept, 2,29-dithio-bis-ethanesulfonate) has also shown some cytoprotective activities in vitro [174].…”
Section: Detoxicantsmentioning
confidence: 99%
“…the results of treatment. Early efforts were focused on reducing the acute and chronic radiation-associated morbidity with the use of the radioprotectant amifostine 17 as well as to the use of alfa-interferon concurrent with pelvic radiation as a radiosensitizer 18 . This latter approach, yet effective, was too toxic to be further pursued.…”
Section: Cervical Cancer the Case Of Mexicomentioning
confidence: 99%